2019
DOI: 10.2478/hepo-2019-0027
|View full text |Cite
|
Sign up to set email alerts
|

Variability of composition of essential oil and coumarin compounds of Angelica archangelica L.

Abstract: SummaryThe medicinal and culinary properties of Angelica archangelica L. have been known and valued since the Middle Ages. Ingredients of essential oil and coumarins found in this plant are to a large degree responsible for its pharmacological activity. This study is a review of the literature of the most important biologically active compounds present in herbal raw materials: root (rhizome with roots) and angelica fruits. Research shows that the content of individual compounds of the essential oil and coumari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…A review of the literature regarding the content of the most important active compounds in A archangelica plant materials confirms the occurrence of large chemical variations within this species [17]. However, the only source of plant material is the angelica root (Angelica radix) of subsp.…”
Section: Introductionmentioning
confidence: 77%
“…A review of the literature regarding the content of the most important active compounds in A archangelica plant materials confirms the occurrence of large chemical variations within this species [17]. However, the only source of plant material is the angelica root (Angelica radix) of subsp.…”
Section: Introductionmentioning
confidence: 77%
“…Contrary to some authors, who describe some characteristics as useful for Angelica species identification, followed by studies in which even subspecies can be clearly distinguished, [22,31,32], there are also scientists who claim that the genus Angelica has highly variable morphological traits, which leads to difficulty in recognition of both species and infraspecific taxa [21,33,34]. By comparing the native range of the above infraspecies taxa, geographical separation in four areas is noticeable.…”
Section: Biological Characteristicsmentioning
confidence: 98%
“…Plant A. archangelica possesses several pharmacological activities. In the traditional medicinal system, it has been implicated in the disorders of the digestive system, blood dyscrasias, immunity booster, and as a uterine tonic (Forycka & Buchwald, 2019). Preclinical studies have revealed that it possesses a wide array of pharmacological activities.…”
Section: Pharmacological Activities Explored For a Archangelicamentioning
confidence: 99%
“…Imperatorin is the major furanocoumarin found in the fruits of the plant. The composition of coumarins varies according to the type of raw material, method of extraction, geographic diversity, extraction conditions, and growing conditions (Forycka & Buchwald, 2019). Coumarins are documented for a variety of pharmacological activities in preclinical investigations, such as analgesic (Kaur et al, 2020a), antiinflammatory activity (Grover & Jachak, 2015), anti‐anxiety activity (Budzynska et al, 2012; Kumar et al, 2013), antioxidative activity (Cao, Zhang, Wang, & He, 2014; Kaur, Garg, et al, 2020a; Kaur, Singh, et al, 2020b), and antiseizure activity (Luszczki et al, 2007; Luszczki, Andres‐Mach, Gleńsk, & Skalicka‐Woźniak, 2010).…”
Section: Coumarinsmentioning
confidence: 99%